Mitochondrial quality control: Cell-type-dependent responses to pathological mutant mitochondrial DNA. Issue 11 (1st November 2016) - Malena, Adriana; Pantic, Boris; Borgia, Doriana; Sgarbi, Gianluca; Solaini, Giancarlo; Holt, Ian J.; Spinazzola, Antonella; Perissinotto, Egle; Sandri, Marco; Baracca, Alessandra; Vergani, Lodovica
ABSTRACT: Pathological mutations in the mitochondrial DNA (mtDNA) produce a diverse range of tissue-specific diseases and the proportion of mutant mitochondrial DNA can increase or decrease with time via segregation, dependent on the cell or tissue type. Previously we found that adenocarcinoma (A549.B2) cells favored wild-type (WT) mtDNA, whereas rhabdomyosarcoma (RD.Myo) cells favored mutant (m3243G) mtDNA. Mitochondrial quality control (mtQC) can purge the cells of dysfunctional mitochondria via mitochondrial dynamics and mitophagy and appears to offer the perfect solution to the human diseases caused by mutant mtDNA. In A549.B2 and RD.Myo cybrids, with various mutant mtDNA levels, mtQC was explored together with macroautophagy/autophagy and bioenergetic profile. The 2 types of tumor-derived cell lines differed in bioenergetic profile and mitophagy, but not in autophagy. A549.B2 cybrids displayed upregulation of mitophagy, increased mtDNA removal, mitochondrial fragmentation and mitochondrial depolarization on incubation with oligomycin, parameters that correlated with mutant load. Conversely, heteroplasmic RD.Myo lines had lower mitophagic markers that negatively correlated with mutant load, combined with a fully polarized and highly fused mitochondrial network. These findings indicate that pathological mutant mitochondrial DNA can modulate mitochondrial dynamics and mitophagy in a cell-type dependent manner and thereby offer an explanation for the persistence and accumulation of deleterious variants.